2005
DOI: 10.1104/pp.104.055244
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics of Eukaryotic Photosynthesis Using Insertional Mutagenesis of Chlamydomonas reinhardtii  

Abstract: The unicellular green alga Chlamydomonas reinhardtii is a widely used model organism for studies of oxygenic photosynthesis in eukaryotes. Here we describe the development of a resource for functional genomics of photosynthesis using insertional mutagenesis of the Chlamydomonas nuclear genome. Chlamydomonas cells were transformed with either of two plasmids conferring zeocin resistance, and insertional mutants were selected in the dark on acetate-containing medium to recover lightsensitive and nonphotosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
200
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(210 citation statements)
references
References 58 publications
7
200
0
Order By: Relevance
“…We observed that in 77 % of the transformants analysed, the insertion took place in intragenic regions. This rate is similar to that observed by Dent and coworkers [20] and González-Ballester and coworkers [21] in functional genomic studies of photosynthesis and the regulation of nitrate assimilation, respectively. In all cases the marker insertion has occurred within a predicted gene or very near one, so identification of the gene responsible for the observed phenotype, has been done considering that the gene interrupted is the most probable responsible of the observed phenotype.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We observed that in 77 % of the transformants analysed, the insertion took place in intragenic regions. This rate is similar to that observed by Dent and coworkers [20] and González-Ballester and coworkers [21] in functional genomic studies of photosynthesis and the regulation of nitrate assimilation, respectively. In all cases the marker insertion has occurred within a predicted gene or very near one, so identification of the gene responsible for the observed phenotype, has been done considering that the gene interrupted is the most probable responsible of the observed phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…This approach has allowed isolation of mutants affected in different metabolic and physiological aspects [14] and has become a popular method for forward genetics studies because identification of the affected genomic region is generally easier than location of genomic lesions caused by traditional mutagenesis procedures based on chemical or physical agents. In C. reinhardtii, this technique has allowed the isolation of mutants affected in flagellar function [15], phototaxis [16], microtubules [17], carbon assimilation [18], H 2 production [19], photosynthesis [20], nitrogen [21] and sulphur metabolism [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transmission pattern of the dark -and Hyg R loci in crosses were determined by random analysis of the meiotic products. Amplification of insertion-linked sequence by thermal asymmetric interlaced (TAIL)-PCR was conducted with degenerate primers as described in (Dent et al, 2005) with APH7 (hygromycine) specific primers: Hygterm1 (5"-CCGCGAACTGCTCGCCTTCACCT -3"), Hygterm2 (5"-TTCGAGGAGACCCCGCTGGATC-3"), and Hygterm3 (5"-CGATCCGGAGGAACTGGCGCA-3").…”
Section: Insertional Mutagenesismentioning
confidence: 99%